Clinical Influence of Different Intracanal Medications on Th1-type and Th2-type Cytokine Responses in Apical Periodontitis - Martinho, Frederico Canato [UNESP]; Nascimento, Gustavo G.; Leite, Fabio R. M.; Gomes, Ana P. M. [UNESP]; Freitas, Lilian F.; Camoes, Izabel C. G. (Elsevier B.V., 2015)
Introduction: This clinical study assessed the influence of different intracanal medications on Th1-type and Th2-type cytokine responses in apical periodontitis and monitored the levels of bacteria from primarily infection during endodontic procedures. Methods: Thirty primarily infected teeth were randomly divided into 3 groups according to the medication selected: chlorhexidine (CHX), 2% CHX gel; Ca(OH)2/SSL, Ca(OH)2 + SSL; and Ca(OH)2/CHX, Ca(OH)2 + 2% CHX gel (all, n = 10). Bacterial sample was collected from root canals, and the interstitial fluid was sampled from lesions. Culture techniques were used to determine bacterial counts (colony-forming units/mL). Th1 (tumor necrosis factor-a, interferon-gamma, and interleukin [IL]-2) and Th2 cytokines (IL-4, IL-5, and IL-13) were measured by enzyme-linked immunosorbent assay. Results: All intracanal medication protocols were effective in reducing the bacterial load from root canals (all P < .05) and lowering the levels of Th1-type cytokines in apical lesions (all P < .05), with no differences between them (P > .05). Both Ca(OH)2 treatment protocols significantly increased the levels of Th2-type cytokines (P < .05), with no differences between them (P > .05). Thus, chlorhexidine medication showed the lowest effectiveness in increasing the levels of Th2-type cytokine. After treatment, regardless of the type of medication, the linear regression analysis indicated the down-regulation of Th2-type cytokines by Th1-type cytokines. Conclusions: All intracanal medication protocols were effective in reducing bacterial load and lowering the levels of Th1-type cytokines. Thus, the use of Ca(OH)2 medications contributed to the increase in the Th2-type cytokine response in apical periodontitis.
Keywords: Disinfection; endodontics; medication; root canal